2006
DOI: 10.3171/foc.2006.20.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of juxtafacet cysts

Abstract: ✓ Juxtafacet cysts are lesions that are associated with spinal facet joints. Although these lesions are frequently noted as incidental findings on imaging studies of the spine, they may produce symptoms in some patients. Juxtafacet cysts can mimic herniated discs, resulting in symptoms from focal nerve root and/or spinal cord compression. Some of these lesions are associated with spinal instability, and patients may require spinal fusion to address this underlying disorder. Conservative therapy for sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Some surgeons prefer simple removal of cyst and others recommend instrumentation and fusion2,17). Many articles report that the juxtafacet cyst has inherent segmental instability4,5,13,14,17). Niggemann et al reported high rate of vertebral slip and angular movement in the affected segment14).…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons prefer simple removal of cyst and others recommend instrumentation and fusion2,17). Many articles report that the juxtafacet cyst has inherent segmental instability4,5,13,14,17). Niggemann et al reported high rate of vertebral slip and angular movement in the affected segment14).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research has suggested that deoxyribonucletic acid ploidy status and proliferative index might be related to the potential for recurrence [6]. There have been no reports focused strictly on the value of various surgical procedures (some authors recommend wide synovectomy and/or laminectomy), although it is important to totally remove the synovium in order to prevent the recurrence [5]. In our case, a total synovectomy with a unilateral osteoplastic laminectomy was performed.…”
Section: Discussionmentioning
confidence: 77%
“…The occurrence of PVNS in the axial skeleton is quite rare and there have been few reports of PVNS of the lumbar spine; specifically, only 18 cases are found in the English literature [4,7,8,10,16,21,23,24,26,27,30,31]. There have been no reports focusing on surgical treatment for PVNS although it is important that the synovium is totally removed to prevent the recurrence [5]. We successfully treated a case of PVNS that originated from the lumbar facet joint (L4-5) using total synovectomy with unilateral osteoplastic laminectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Although juxtafacet cysts may occur throughout the spine they occur most frequently in the lumbar spine [43] and some consider the occurrence associated with spinal instability and/or spondylolisthesis.…”
Section: Aetiology/epidemiologymentioning
confidence: 99%